The Africa Growth and Opportunity Act and its Rules of Origin : Generosity Undermined? - Mattoo, Aaditya (World Bank, Washington, DC, 2014)
The African Growth and Opportunity Act (AGOA), signed into American law on May 18, 2000, is a major plank of U.S. initiatives toward the African continent. The Act aims broadly at improving economic policymaking in Africa, enabling countries to embrace globalization, and securing durable political and economic stability. As an incentive for Africa to adopt the necessary policy reform, AGOA offers increased preferential access for African exports to the United States. This paper describes the provisions of AGOA and assesses its quantitative impact on African exports, particularly in the apparel sector. Its main conclusions are: 1) AGOA will provide real opportunities to Africa. Even on conservative estimates about Africa's supply response, Africa's non-oil exports could be increased by about 8-11 percent. 2) However, the medium-term gains could have been much greater if AGOA had not imposed certain conditions and not excluded certain items from its coverage. The most important condition is the stringent rule-of-origin, that is, the requirement that exporters source certain inputs from within Africa or the United States. Estimates suggest that the absence of these conditions would have magnified the impact nearly five-fold, resulting in an overall increase in non-oil exports of US$0.54 billion compared with the US$100-US$140 million increase that is expected in the presence of these restrictions. These restrictions, particularly on apparel, will come at a particularly inopportune time, as Africa will be exposed to competition from other developing countries when the quotas maintained on the latters' exports under the Multi-Fiber Arrangement (MFA) are eliminated. Africa's apparel exports will be lower by over 30 percent with the dismantling of the MFA. If, on the other hand, AGOA had provided unrestricted access, the negative impact of the dismantling could be nearly fully offset.